THE ROLE OF MICRO FINANCIAL INSTITUTION TO IMPROVE SOCIO-ECONOMIC OF THE RURAL COMMUNITIES - Moh. Aziz Arisudi; Salfarina Abdul Gapor (Jurnal Keuangan dan Perbankan, 2010)
Micro f inancial inst itut ion had an important role to improve the socio-economicof the rural communit ies. However, in its effort , the result in improving the socio-economicof the rural communit ies, part icularly among the poor is st ill low. The access for the ruralcommunit ies for low interest credit was also limited. The object ives of this research were asfollows. First , to analyze the factors that drove the rural communit ies to borrow money f rommicro credit inst itut ions. Second, to analyze the role of micro credit inst itut ions and itsimpacts on the rural communit ies socio-economic, Third, to analyze the rural communit iescoping st rategies, Fourth, to evaluate the rural communit ies percept ions on micro creditinterest rate. This research used both qualitat ive and quant itat ive methods. The results ofthis research were as follows. First , the factors causing rural communit ies to borrow moneyf rom micro credit inst itut ions were to cover their living cost , provision and addit ion of capital.The micro credit inst itut ion had considerably lower interest rate than rentener, and theprocedures were simple and fast . Second, the role of micro credit inst itut ions to improve therural communit ies socio-economic was st ill low. Third, the interest rate of the micro creditinst itut ions was comparably fair and lower than the unlicensed micro bank.